PENGARUH PROFITABILITAS, LEVERAGE, DAN SALES GROWTH TERHADAP CASH HOLDING - Owen, Nakanael; Nariman, Augustpaosa (Jurnal Paradigma Akuntansi, 2025)
Nowadays, cash became a standard to measure a company ability in money management. There have been many studies on cash holding but came with inconsistent results. This study aims to determine the effect of profitability, leverage, and sales growth on cash holding in manufacturing companies listed on the Indonesia Stock Exchange during 2018-2020. The number of research samples was 204 data, which were selected using purposive sampling method. The hypothesis testing model uses multiple regression analysis with the help of Eviews 12 and Microsoft Excel 2010. The results of this study shows that profitability has a significant positive effect on cash holding, leverage has a significant negative effect on cash holding, and sales growth has no effect on cash holding.